Arquitetura Baseada em Redes Definidas por Software para Gestão de Aplicações e Comunicação em Plataformas IoT de Baixo Custo - Lima, Luis Eduardo [UNIFESP] (2022)
In the literature, the application of the Software-Defined Network (SDN) concepts with com Internet of Things (IoT) architectures has been used to reduce the complexity of the configuration and management of these networks. In this research we proposed a new architecture using SDN capabilities to remote reprogramming the application layer, avoiding the firmware update, in order to increase the flexibility of the networks and allow the implementation in very low cost devices. We validated the proposed architecture in a simulation environment by evaluating several scenarios considering end-to-end delay, delivery ratio, network lifetime and control overhead. In addition, we developed a prototype of the architecture and performed an experimental evaluation considering the same metrics used in the simulation evaluation. As a result, we verified that the end-to-end delay, the delivery ratio and the control overhead presented values compatible with those expected for IoT applications. The cost of the nodes used in this research represented a minimum discount of 82% to the value of the nodes of the architectures found in the literature. The operation of remote reprogramming of the application layer was evaluated and it was found that the amount of memory used to implement the architecture is compatible with the storage capacity of very low-cost devices. The results obtained in the simulations and in the experiments evince the functionalities of the architecture in the tested scenarios and confirmed the flexibility using SDN resources for remote reprogramming of the application layer. In this way, the proposed architecture can be deployed on low-cost devices and used for testing and experimental validation of new applications and solutions focused on routing, security and encryption, authentication, among others.